Citizen participation in international events held in Mexico (Ministry of Foreign Affairs Mexico CityMX, 2018)
Mexican foreign policy has played an important role in the plural articulation of several voices of Mexican society and its inclusion in the negotiation and strengthening processes of national decisions. True to its multilateralist tradition, Mexico has been distinguished as an excellent host of international events such as the 16 described in this document. In each of them, citizen participation stands out as a hallmark of the added value that the inclusion of diverse actors brings to the spaces of an inclusive multilateralism, which Mexico strongly supports.
Keywords: INTERNATIONAL RELATIONS